An efficient photothermal–chemotherapy platform based on a polyacrylamide/phytic acid/polydopamine hydrogel. Issue 21 (4th May 2022) - Zhao, Zhen; Zhang, Hua; Chen, Hongda; Xu, Yuanhong; Ma, Lina; Wang, Zhenxin
Abstract : An effective platform for chemophotothermal therapy based on a polyacrylamide/phytic acid/polydopamine hydrogel was constructed and applied to tumor treatment with its highly efficient drug loading and photothermal heating properties. Abstract : In this work, the polyacrylamide/phytic acid/polydopamine (termed as PAAM/PA/PDA) hydrogel is used as a drug loading matrix and photothermal conversion reagent, which is prepared by copolymerization of dopamine with acrylamide through a phytic acid crosslinker. Due to the porous structure of PAAM and strong near-infrared light (NIR)-absorption of PDA, the PAAM/PA/PDA hydrogel exhibits a high doxorubicin (DOX)-loading capacity (170 mg g −1 ) and efficient photothermal transduction efficiency (47.4%) even under low power density 808 nm NIR laser (0.75 W cm −2 ) irradiation, which is superior to those of most conventional photothermal conversion agents reported in the literature. With NIR laser irradiation, the PAAM/PA/PDA hydrogel loaded with DOX (termed as PAAM/PA/PDA/DOX) shows excellent synergistic interaction between photothermal therapy (PTT) and enhanced chemotherapy, resulting in the completely suppressed growth of mouse-bearing SW620 tumors. Furthermore, the PAAM/PA/PDA hydrogel shows good physicochemical stability, negligible cytotoxicity and low toxicity in vivo . All these characteristics render the as-prepared PAAM/PA/PDA hydrogel promising for biomedical applications.